2021
DOI: 10.1108/jacpr-08-2020-0535
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems, family functioning and social support among children survivors of Colombia’s armed conflict

Abstract: Purpose Colombia presents with one of the largest armed conflicts in the world. Children exposed directly or indirectly to armed conflicts live the emotional footprints left by war. This paper aims to identify mental health problems among children survivors of Colombia’s armed conflict and associated factors. Design/methodology/approach A cross-sectional study with (n = 80) children aged 7 to 11 years (M = 9.8 years; SD = 1.4) was conducted using the Child Behavior Checklist, Family APGAR and MOS social supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
0
8
0
2
Order By: Relevance
“…Other studies that have used the MOS Social Support Survey suggest that social support is related to family functioning (Sánchez-Villegas et al, 2021), marital status (Coyle, 2011), or family functionality (Casanova-Rodas et al, 2014). For nurses and professionals working with families, social support would then represent a key point of reinforcement to maintain and improve family health by promoting healthy, close, and available social support relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that have used the MOS Social Support Survey suggest that social support is related to family functioning (Sánchez-Villegas et al, 2021), marital status (Coyle, 2011), or family functionality (Casanova-Rodas et al, 2014). For nurses and professionals working with families, social support would then represent a key point of reinforcement to maintain and improve family health by promoting healthy, close, and available social support relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several of these studies also reported that factors relating to social support were associated with better mental health outcomes in adolescents affected by violence and displacement cross-sectionally. Sánchez-Villegas et al (2021) reported family functioning and social support was associated with fewer emotional and behavioural problems, Sánchez Acosta et al (2019) reported the same factors reduced the odds of CIDI diagnosed mental health problems, suicidal behaviour and substance use, and Gaias et al (2019) reported positive school climate reduced the risk of externalising behaviours. Using the 2015 NMHS dataset, Gómez-Restrepo et al (2021) reported that family dysfunction and economic disadvantage was associated with increased self-recognition of mental health problems in Colombian adolescents.…”
Section: Family Functioning But Not Social Capital Is Associated With...mentioning
confidence: 95%
“…Social and emotional support and having good social relations were shown to contribute to less depression symptoms [11 ••, 80••], reduced PTSS and anger [6], less behavior problems [81], greater optimism and satisfaction with life [53••], and greater post-traumatic growth [60]. Key protective factors were youth supportive relationships and social participation [81]; neighborhood attachment, such as having a close friend, which was associated with optimism and life satisfaction [53••]; and social cohesion, such as feeling part of a group and spending time with friends, which was associated with better self-reported health [53••]. In addition, community coherence and community support resources were resilience factors explaining various mental health problems, including internalizing and externalizing problems and PTSD [40••].…”
Section: Children's Support Networkmentioning
confidence: 99%